Enhanced toughness and thermal properties of bismaleimide resin based on the synergistic effect of reactive amino‐terminal poly(phthalazinone ether nitrile sulfone) and bisallyl bearing diphenol group. (30th November 2020) - Liu, Cheng; Jia, Hang; Li, Nan; Qiao, Yue; Weng, Zhihuan; Du, Gaize; Jian, Xigao
Abstract : Bismaleimide (BMI) resins have poor toughness due to their high crosslink density, which limits their wide development and application. In this study, the amino‐terminated poly(phthalazinone ether nitrile sulfone) (PPENS‐DA) resin was designed and the curing agent of 3, 3′‐diallyl‐4, 4′‐biphenol (DABP) was synthesized to toughen N, N ′‐(4, 4′‐diphenylmethane) bismaleimide (BDM) resin. The impact strength, flexural strength and fracture surface structures of the DABP/BDM and PPENS‐DA/DABP/BDM blends were studied. The results showed that the notched impact strength of the blends with 10‐phr PPENS‐DA is 4.98 kJ/m 2, which was 36% higher than that of pristine BDM/DABP blend and 200% higher than that of the 2, 2′‐diallyl bisphenol A (DABPA) modified BMI resin system. The glass transition temperature ( T g ) has been improved from 247 to 269°C for the blend system as evidenced by DMA. Rheological behavior analysis indicated that the blend system has a broad processing window (90‐175°C) with low viscosity of less than 1 Pa·s and low curing activation energy of 67.2 kJ/mol.